Box Design Selection for Portable Minapadi Based on Hydrostatic and Thermal Loading Simulation - Tri Julianto, Baskoro; Setiawan , Budi Indra; Saptomo, Satyanto Krido (PERTETA, 2024)
Land conversions pose a threat to food security. Urban agriculture is considered to be a solution to this issue. Urban agricultural innovations are diverse, including vertiminaponics, cube-model microirrigation, and Nonpowered Automatic Fertigation systems. The development of a powerless automatic fertigation innovation involves creating a portable Minapadi concept by substituting some components, such as pots, with fiberglass boxes. This study aims to achieve a good box design to support the concept of urban agriculture. The study began by testing 10 fiberglass samples on a UTM machine to obtain the mechanical properties of the material, such as the modulus of elasticity, which were input into a computer simulator along with other physical and mechanical properties. The computer-aided simulator used was the ANSYS 2024 R2 Student software, simulating two potential box designs: the first box had a thickness of 4 mm with a lateral support in the middle of its vertical span, while the second box had a thickness of 6 mm without lateral support. Loading was applied hydrostatically with water level heights ranging from 50 to 400 mm and thermal loading simulating solar radiation. The results of this study show that solar radiation has a minimal impact on box deformation, whereas water-level height plays a significant role in box deformation. The first box design was considered the best based on deformation due to hydrostatic pressure, with a maximum deformation of 2.175 mm under hydrostatic loading with a water level height of 400 mm.